Nanomaterials in the Management of Gram-Negative Bacterial Infections - Barani, Mahmood; Zeeshan, Mahira; Kalantar-Neyestanaki, Davood; Farooq, Muhammad; Rahdar, Abbas; Jha, Niraj; Sargazi, Saman; Gupta, Piyush; Thakur, Vijay (Nanomaterials (Basel, Switzerland), 2021)
The exploration of multiplexed bacterial virulence factors is a major problem in the early stages of Escherichia coli infection therapy. Traditional methods for detecting Escherichia coli (E. coli), such as serological experiments, immunoassays, polymerase chain reaction, and isothermal microcalorimetry have some drawbacks. As a result, detecting E. coli in a timely, cost-effective, and sensitive manner is critical for various areas of human safety and health. Intelligent devices based on nanotechnology are paving the way for fast and early detection of E. coli at the point of care. Due to their specific optical, magnetic, and electrical capabilities, nanostructures can play an important role in bacterial sensors. Another one of the applications involved use of nanomaterials in fighting microbial infections, including E. coli mediated infections. Various types of nanomaterials, either used directly as an antibacterial agent such as metallic nanoparticles (NPs) (silver, gold, zinc, etc.), or as a nanocarrier to deliver and target the antibiotic to the E. coli and its infected area. Among different types, polymeric NPs, lipidic nanocarriers, metallic nanocarriers, nanomicelles, nanoemulsion/ nanosuspension, dendrimers, graphene, etc. proved to be effective vehicles to deliver the drug in a controlled fashion at the targeted site with lower off-site drug leakage and side effects.